2020
DOI: 10.36227/techrxiv.12911321.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Blockchain and Technologies Matching with the Case of Study of Vegetables Production

Abstract: <div>Alessandro Massaro: Professor Alessandro Massaro (ING/INF/01, FIS/01,FIS/03) carried out scientific research </div><div>at the Polytechnic University of Marche, at CNR, and at Italian Institute of Technology (IIT) as Team Leader by activating laboratories for nanocomposite sensors for </div><div>industrial robotics. He is in MIUR register as scientific expert in competitive Industrial Research and social </div><div>develo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…A scalable, modular, low-cost IOT/smart agriculture (SA)-oriented management platform called VegIoT Garden, which is based on commercial-off-the-shelf (COTS) devices, is designed to support farmers in improving the commodities they produce, identifying key issues, and addressing irrigation-related issues, identifying possible correlations between climate characteristics, and this paper presents field productivity and crop health [142]. To study the blockchain and technology that match vegetable production, Massaro et al [143] described the entire scenario and the use of blockchain technology and concluded that the technology and methods used in the literature are suitable for quality traceability. It is also useful to apply other supplies.…”
Section: Vegetablesmentioning
confidence: 99%
“…A scalable, modular, low-cost IOT/smart agriculture (SA)-oriented management platform called VegIoT Garden, which is based on commercial-off-the-shelf (COTS) devices, is designed to support farmers in improving the commodities they produce, identifying key issues, and addressing irrigation-related issues, identifying possible correlations between climate characteristics, and this paper presents field productivity and crop health [142]. To study the blockchain and technology that match vegetable production, Massaro et al [143] described the entire scenario and the use of blockchain technology and concluded that the technology and methods used in the literature are suitable for quality traceability. It is also useful to apply other supplies.…”
Section: Vegetablesmentioning
confidence: 99%
“…Concerning irrigation and FER advances, specific methods can be adopted using DSS models based on data field detection Massaro & Meuli et al, 2018) and data fusion approaches (D' Accolti et al, 2018). Another technology useful for the traceability of field production processes is the blockchain (Massaro & Maritati et al, 2020). The described state of the art, highlights that the FER technologies and approaches can be different.…”
Section: Introductionmentioning
confidence: 99%